Character’s Selection of Leaf Morphology in Some Families (Tree Habit) In Sumatra Region for Species Identification - Saida Rasnovi (Universitas Syiah Kuala, 2013)
Identification is a basic activity and one of primary objective on systematic. For plant biodiversity studies,it was the first steps that researcher performed before studying any topics in the research area. Unfortunately, species identification is usually a time consuming activity. One of the main objectives of this study was to obtain a set of leaf morphology characters that were useful and efficient enough for species identification, especially on the tree habits group in order to reduce time consuming for the identification species. All of the leaf morphology characters were selected by correlation coefficient and separation coefficient values. Besides of that, the stability, simplicity and validity of the characters were also part of concern. The characters that had high value of separation coefficient and low value of correlation coefficient would be added one by one as in their rank, until the value of the combination separation coefficient was equal to 1 (100%). The result of this study suggested that 30 from 92 characters of leaf morphology were recommended as a set of characters that useful and efficient enough for species identification.